The Relationship between Eco-friendly Practices and Attitudes toward Green Hotels for Domestic Tourists - Nguyen, Thi Phuong Thao (H. : ĐHQGHN, 2017)
Green management is an inevitable trend in the hotel industry as a response to the needs of sustainable development. However the common question is whether tourists care about the environmental protection measures of hotels. This study sets out to examine the relationship between green activities in hotel rooms and the attitude of tourists. The results of the study have confirmed that the attitudes of hotel guests are positively related to their preference for green practices. Among all factors, the utilization of new technology appliances has the strongest influence on guests’ attitude. Based on the research result, it is suggested that the hotelier should employ new technology appliances as well as launch plenty of environmentally friendly policies in order to obtain a positive attitude from their customers.